Theorical concepts in the search of health as universal right - Rodríguez Torres, Alejandra (2015)
Health is a social construction which involves historical moments and social development. Trying to understand the health as a universal human right is to understand the different theoretical currents that have existed around until encountering salutogenesis. Which leads us to understand health from the principles of otherness, dignity and solidarity, where the collective and the individual are essential to take part in decision about health as social practice of the community.